Clinical Development and Commercialization of Advanced Therapy Medicinal Products in the European Union: How Are the Product Pipeline and Regulatory Framework Evolving? - Boráň, Tomáš; Menezes-Ferreira, Margarida; Reischl, Ilona; Celis, Patrick; Ferry, Nicolas; Gänsbacher, Bernd; Krafft, Hartmut; Lipucci di Paola, Michele; Sladowski, Dariusz; Salmikangas, Paula (Human gene therapy. Clinical development, 2017)
The research and development of advanced therapy medicinal products (ATMPs) has been active in Europe and worldwide during recent years. Yet, the number of licensed products remains low. The main expected legal change in the near future in the European Union (EU) concerns the regulation on clinical trials (536/2014), which will come into force in 2018. With this new framework, a more harmonized and swift process for approval of clinical trials is anticipated, which is expected to support the entry of new innovations into the EU market. A survey on ATMPs in clinical trials during 2010-2015 in the EU was conducted in order to study the trends of ATMP development since the earlier survey published in 2012. According to the results, the number of clinical trials using ATMPs is slowly increasing in the EU. Yet, the focus is still in early development, and the projects are mainly carried out by small and medium-sized enterprises, academia, and hospitals. Oncology is the main area of clinical development. Yet, the balance between cell-based products and gene therapy medicinal products in this area may be changing in the future due to the new T-cell technologies. Many limitations and challenges are identified for ATMP development, requiring proportionate regulatory requirements. On the other hand, for such a novel field, the developers should be active in considering possible constraints and actively engage with authorities to look for solutions. This article provides up to-date information on forthcoming regulatory improvements and discusses the main challenges hampering the commercialization of ATMPs in the EU.
Keywords: tissue engineering; cell therapy; Clinical Trials as Topic; Drug Industry; ATMP; Evropská unie; gene therapy; Biomedical Research; clinical trials; farmaceutický průmysl; Technology Transfer; biomedicínský výzkum; klinické zkoušky jako téma; transfer technologií; European Union